How Useful Is Preoperative Aspiration before Revision of Unicompartmental Knee Prostheses Because of Osteoarthritis in the Other Compartments? - Benedikt Paul Blersch; Florian Hubert Sax; Bernd Fink (MDPI AG, 2024)
Aim: Periprosthetic joint infections (PJIs) of unicompartmental knee arthroplasties (UKAs) can lead to secondary osteoarthritis of the other compartments. The objective of this study was to identify the frequency of PJIs in cases of UKA with progressed secondary osteoarthritis and the result of septic one-stage revision in these cases to verify the value of preoperative aspiration in cases of secondary osteoarthritis of UKA. Methods: We retrospectively reviewed 97 patients with a unicompartmental arthroplasty who underwent revision surgery to a total knee arthroplasty (TKA) between January 2013 and March 2021 because of subsequent osteoarthritis. Preoperative aspiration and sample collection during the revision surgery were employed to identify potential periprosthetic joint infections (PJIs). The post-revision period was monitored for septic complications over an average duration of 55.7 ± 25.2 months (24-113). Results: PJIs were identified in 5.2% of cases through preoperative aspiration. In all instances of PJIs, a one-stage septic revision was performed, and notably, none of these cases experienced septic complications during the follow-up period. Conclusions: Preoperative aspiration is essential in order to exclude the presence of a PJI before performing revision surgery of UKA due to secondary osteoarthritis.